Socioeconomic inequalities in the rate of stillbirths by cause: a population-based study. Issue 3 (25th June 2012) - Seaton, Sarah E; Field, David J; Draper, Elizabeth S; Manktelow, Bradley N; Smith, Gordon C S; Springett, Anna; Smith, Lucy K
Abstract : Objective: To assess time trends in socioeconomic inequalities in overall and cause-specific stillbirth rates in England. Design: Population-based retrospective study. Setting: England. Participants: Stillbirths occurring among singleton infants born between 1 January 2000 and 31 December 2007. Main outcome measure: Cause-specific stillbirth rate per 10 000 births by deprivation tenth and year of birth. Deprivation measured using the UK index of multiple deprivation at Super Output Area level. Methods: Poisson regression models were used to estimate the relative deprivation gap (comparing the most and least deprived tenths) in rates of stillbirths (overall and cause-specific). Excess mortality was calculated by applying the rates seen in the least deprived tenth to the entire population at risk. Discussions with our local NHS multicentre ethics committee deemed that this analysis of national non-identifiable data did not require separate ethics approval. Results: There were 44 stillbirths per 10 000 births, with no evidence of a change in rates over time. Rates were twice as high in the most deprived tenth compared with the least (rate ratio (RR) 2.1, 95% CI 2.0 to 2.2) with no evidence of a change over time. There was a significant deprivation gap for all specific causes except mechanical events (RR 1.2, 95% CI 0.9 to 1.5). The widest gap was seen for stillbirths due to antepartum haemorrhages (RR 3.1, 95% CI 2.8 to 3.5). No evidence of a change in the rate of stillbirth or deprivation gap over time was seen for any specific cause. Conclusion: A wide deprivation gap exists in stillbirth rates for most causes and is not diminishing. Unexplained antepartum stillbirths accounted for 50% of the deprivation gap, and a better understanding of these stillbirths is necessary to reduce socioeconomic inequalities.